From sustainable to resilient cities global concerns and urban efforts - Holt, William G. (Bingley, U.K. : Emerald, 2014)
The United Nations Brundtland Report defines sustainable development as one 'that meets the needs of the present without compromising the ability of future generations to meet their own needs." Embedded in this concept of sustainable development are the needs of the world's poor as well as the limits of environmental technology and social organizations to meet these needs. Urban centers, home to the majority of world's population, are hubs of sustainability innovations. However there are major differences among how these sustainability issues are addressed in the Global North and South. Increasingly, urban areas are moving from sustainability to resilience in dealing with environmental issues. This edited volume addresses sustainability efforts in cities and metropolitan regions around the world. The edition explores sustainable development across four key areas: environment, economic, socio-political, and cultural sustainability. These concepts are examined as they apply to both Global North and South urban areas. This volume includes chapters about applications to urban regions across the globe focusing on the movement from sustainable development to resilient urban centers.
Sustainable cities in flux : continuity, comparisons, and conceptions / Yifei Li -- Coping with natural disasters and urban risk : an approach to urban sustainability from socio-environmental fragmentation and urban vulnerability assessment / Felipe Link ... [et al.] -- Towards sustainable urban and regional planning : experiences from the Netherlands / Bart Wissink -- Residential landscapes, environmental sustainability and climate change / Steven B. Scyphers, Susannah B. Lerman -- Urban crisis within environmental and industrial policies in Italy : the case of the steel industry in Taranto / Mara Maretti -- Sustainable cities in post-Soviet Central Asia : the case of Bishkek / Daniel M. Cartledge -- Sustainability challenges and the spatial manifestation of poverty in megacities of the global south : focus on Dhaka, Bangladesh / Saleh Ahmed, Khan Rubayet Rahaman -- Smart growth machines : the ecological modernization of urban political economy / Erik Solevad Nielsen -- Creating new urban spaces of sustainability and governmentality : an assessment of the development of a food and urban agriculture strategy for Edmonton, Canada / Lorelei L. Hanson, Deborah Schrader -- Línea Verde, an axis road in Aguascalientes, Mexico / Edgar Ramírez de la Cruz, Edna Liliana Gómez Fernández -- Barriers to sustainability : gendered divisions of labor in Cuban urban agriculture / Christina Ergas -- Do you know what it means to rebuild New Orleans? Cultural sustainability after disaster / William G. Holt -- "The world is my backyard" : romanticization, Thoreauvian rhetoric, and constructive confrontation in the tiny house movement / April Anson -- Becoming an European green capital : a way towards sustainability? / Ilaria Beretta -- From sustainability to resilience : why locality matters / Lily M. Hoffman.
Print version record
Keywords: Social Science -- Sociology -- Urban; Sociology; Sociology & anthropology; Urban & municipal planning; Sustainable urban development; City planning -- Environmental aspects